Overpaid or underpaid? A state-by-state ranking of public-employee compensation - Andrew G. Biggs; Jason Richwine (American Enterprise Institute (AEI), 2014)
This paper ranks all 50 states according to how costly their public-employee compensation packages are relative to private-sector standards. Each state's package is placed into one of five categories: modest penalty, market level, modest premium, large premium, or very large premium. The results show that national-level analyses obscure significant differences in compensation from state to state. Connecticut, for example, pays its state employees 42 percent more than what similar private-sector workers receive, but Virginia pays its state workers about 6 percent less. State-by-state political interest in public-sector pay aligns fairly well with our results: In states where public sector pay is an active political issue, state government employees appear to be better compensated than similarly-skilled private sector workers. In states where state government compensation is at or below market levels, pay for public employees is generally less controversial.
Keywords: A; 330; Public Pensions; Policy Papers